Bioaccumulation and effects of parent and alkylated PAHs in an Arctic marine amphipod (Gammarus setosus) originating from pristine and historically contaminated sites in Svalbard. Implications for sensitivity and adaptation - Alonso, Marina Vázquez (UiT The Arctic University of Norway, 2016)
The objectives of the study were to assess the bioaccumulation and genotoxic effects of PAHs and their alkylated PAHs from marine diesel fuel and coal polluted sediments in two populations of Gammarus setosus. Testing whether the alkylated forms are bioaccumulating more than their parent compounds, the degree of oxidative stress and ulterior DNA SSBs in the amphipods, as well as possible adaptation to toxicity of the pollutants in the two populations. The two populations were exposed during a period of 28 days to three treatments, MDF spiked sediment, naturally coal contaminated sediment and control sediment from a pristine area. PAHs concentrations in both biota and sediment, oxidative stress and DNA damage were quantified at the start of the exposure and during 5 sampling times. A conservative concentration of MDF was spiked (900 mg kg-1 sediment) simulating a non-acute oil spill. Coal samples from the abandoned mining area in Ny-Alesund and Thiisbukta were collected for PAHs quantification.